Green matters [ green building - Drane, Margaret; Drane, Paul; Farrow, Nick; Holmes, Abe; World Wide Entertainment (Greelong,Australia : World Wide Entertainment, 2010)
Information technology giant,wipro, considers its software development centre India's greenest building to date. The development,spread across 1.2 acres of land, has received international recognition for its many eco-friendly features.the building is a model of energy efficiency and environmental friendliness. It takes full advantage of natural lighting, with 75% of the building day-lit, including the spacious reception area
1. Green building -- 2. Netherlands windmills -- 3. Le man biofuel car -- 4. Taiwan recycling -- 5. Urban farmer -- 6. Orangutan baby -- 7. Trash fashion -- 8. Polar trek
Writer/producer, Margaret Drane ; co-producer, Paul Drane ; executive producer, Nick Farrow ; music, Margaret Drane ; post production The Edit Shop
Narration Abbe Holmes
DVD
Keywords: Green technology; Industrial design -- Environmental aspects